A new flow pattern map for flow boiling of R1234ze(E) in a horizontal tube. (January 2018) - Yang, Zhi-Qiang; Chen, Gao-Fei; Zhuang, Xiao-Ru; Song, Qing-Lu; Deng, Zeng; Shen, Jun; Gong, Mao-Qiong
Highlights: The effects of parameters on flow pattern transition were analyzed. Comparisons were made between classical flow pattern maps and experimental data. Five forces were taken into account for the new flow pattern transition models. A new flow pattern map of R1234ze(E) was developed. Abstract: Considerable attention has recently been given to the new environment-friendly refrigerant of R1234ze(E) for applications such as heat pump and air-conditioning systems. In this study, an experiment was carried out to investigate two-phase flow patterns and flow transitions for R1234ze(E) in a smooth horizontal tube with an inner diameter of 6 mm. The experiments were performed at conditions covering saturation pressures from 0.215 to 0.415 MPa, mass fluxes from 130 to 258 kg/m 2 s and heat fluxes from 10.6 to 74.8 kW/m 2 . The influences of saturation pressure, mass flux and heat flux on flow pattern transition were analyzed. Six well-known flow maps have been compared with the observed flow patterns of R1234ze(E). The results indicated that none of them can predict all the flow pattern transitions well. Thus, three dimensionless numbers K 1, K 2 and K 3 which represent the ratio of the evaporation momentum force to the inertia force, the evaporation momentum force to the surface tension force, and the shear force to the gravity force respectively were introduced. Based on dimensionless numbers K 1, K 2, K 3 and X tt, a new flow pattern map for R1234ze(E) was proposed which could accurately predict the experimental data.